ANALISIS SISTEM PENANGANAN PENGADUAN PADA PELAYANAN PERIJINAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA SEMARANG - Bisri, Devitasari Nur Fadzilah; Warsono, Hardi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Public service becomes an important for the government in providing services to the citizen. One of them is giving administration services in DPMPTSP of Semarang City. Till now the administration service is considered difficult by citizen, those which are causing complaints from the public related services. The problem is lack of clarity in the follow-up of complaints that was submitted by the citizen. The purpose of this study is to examine the complaints handling system and the factors that impede the implementation of complaint handling in DPMPTSP Semarang City. The method used is descriptive qualitative. The results showed that on the input aspect of the inhibiting factor is the lack of human resources in handling complaints and frequent disruptions in the internet network. While aspects of the process on the dimensions of commitment showed that the follow-up to the violating community is considered less assertive. In the dimension of clarity, infrastructure facilities regarding the information handling process of the complaint is still unclear. In the output aspect, the complaint handling evaluation program has been carried out on a regular basis. Feedback obtained by the DPMPTSP Semarang City comes from the polling SMS survey of citizen satisfaction (SKM), while from the citizen has felt the development of administration services. Based on these results it is recommended that DPMPTSP Semarang City should add employees to be assigned as staff in handling complaints, increase the quality of internet network, increase assertiveness with sanctioning regulations for society or companies that do not have permission, and improve the facility of information handling complaints to be more clear.